Developing A Cultural Intelligence Instrument for Guidance and Counseling Teachers - Suciani Latif; Uman Suherman AS; Mamat Supriatna; Ilfiandra Ilfiandra (Universitas Negeri Makassar, 2022)
Abstract. The study aimed to produce a self-report instrument using a cultural intelligence scale for Guidance and Counseling teachers. It employed Research and Development design adopting the model of Adam and Wieman (2011). Operationally, the development of the instrument was divided into five stages, 1) determining the question format; 2) determining the question construction; 3) determining the guidance of assessment, expert judgment, and revision of the question; 4) expert judgment by the experts of culture and instrument development; and 5) analyzing instrument using the Rasch model. Data analysis showed that in the development of cultural intelligence instrument: 1) the instrument construct was correctly determined, and it could measure one variable of Guidance and Counseling teachers' cultural understanding; 2) there were five items of cultural intelligence instrument categorized as very difficult and five items were in the very easy category; 3) all items of cultural intelligence instrument of Guidance and Counseling teachers were fit, meaning that it functioned normal, could be understood by the Guidance and Counseling teachers, and can measure what it should measure; and 4) The Cronbach Alpha was 0,96, indicating that the instrument was in the Very Good category with the Person Reliability of 0,92 and Item Reliability of 0,99. Therefore, based on the Rasch model analysis, the cultural intelligence instrument of Guidance and Counseling teachers, which was developed, had fulfilled the set standard and Good criteria, and it could be used to collect data about the cultural intelligence of Guidance and Counseling teachers.